The Effect of Rice Grain Malt Concentration during Hydrolysis of Rice on the Characteristics of Rice Sugar Syrup - Rafael, Fadhil Luthfi; Rahmi, Silvi Leila; Purba, Daniel Tua; Ulyarti, Ulyarti (PUI BiGME Universitas Jambi, 2025)
Malt is the germination product of cereals that contain hydrolytic enzymes capable of breaking down starch. The concentration of rice grain malt is a factor that affects the hydrolysis process of rice (Oryza sativa L.) and the characteristics of the resulting rice sugar syrup. The malt concentrations used in this study were 25%, 35%, 45%, 55%, and 65%. The rice sugar syrup showed positive (+) results for residual starch. The concentration of rice grain malt had a significant effect on total soluble solids, color, organoleptic ranking, and viscosity. The total soluble solids of the rice sugar syrup ranged from 41.95 to 64.95 °Brix. The color difference (ΔE) ranged from 33.410 to 12.648. The viscosity of the rice sugar syrup ranged from 244.8 to 1448.1 cPs. The organoleptic ranking showed that the syrup produced with 65% malt concentration had the highest sweetness level. Hedonic organoleptic scores for color ranged from 3.6 to 3.36, aroma from 3.48 to 3.92, taste from 3.48 to 4.00, viscosity from 3.32 to 4.00, and overall acceptance from 3.56 to 4.16. The rice grain malt concentration of 65%, which was the highest concentration used for rice hydrolysis, produced rice sugar syrup with total soluble solids of 64.95 °Brix, color difference (ΔE) of 12.648, viscosity of 1448.1 cPs, the highest sweetness ranking, and the best favorability.